1962
DOI: 10.1139/f62-054
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Rate of Yolk Utilization by Developing Embryos and Larvae of the Pacific Sardine Sardinops caerulea (Girard)

Abstract: The chemical composition of ripe Pacific sardine ovaries, composed primarily of yolk, is almost identical to that of yolk extracted from planktonic sardine embryos and larvae. Caloric measurements were made on ripe ovaries and the values obtained were used to estimate the caloric content of individual sardine embryos and larvae.Water content of sardine egg and larval yolk averages 91.2%. An egg with a yolk volume of 0.56-mm3 has a caloric reserve of 0.30 calorie when spawned. Caloric uptake from the embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

1974
1974
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 0 publications
0
33
0
2
Order By: Relevance
“…Causes of the very high mortality during this period may include environmental stress, relationships with other organisms (competitors, predators, disease agents), developmental abnormalities, and nutrition deficiency between the time yolk-sac reserves are exhausted and feeding is initiated (Toetz, 1966). The appearance of an energy deficit prior to functional feeding abilities has been observed by Lasker (1962) in the Pacific sardine. Such a deficit would lead to starvation if the ability to feed did not soon develop.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Causes of the very high mortality during this period may include environmental stress, relationships with other organisms (competitors, predators, disease agents), developmental abnormalities, and nutrition deficiency between the time yolk-sac reserves are exhausted and feeding is initiated (Toetz, 1966). The appearance of an energy deficit prior to functional feeding abilities has been observed by Lasker (1962) in the Pacific sardine. Such a deficit would lead to starvation if the ability to feed did not soon develop.…”
Section: Discussionmentioning
confidence: 94%
“…Unfertilized ova were used to determine energy content of yolk; homogenized samples of larvae after total yolk absorption were used to determine the energy content of tissue. It is assumed that the chemical composition of yolk does not change appreciably during larval development (Lasker, 1962) so the energy equivalent obtained from unfertilized ova can be used throughout the development period. It is also assumed that a homogeneous sample of larval tissue provides an average energy equivalent for all tissues produced during larval growth.…”
Section: Methodsmentioning
confidence: 99%
“…This maximal gross growth efficiency for fish larvae is intermediate in value to the efficiency of yolk utilization by fish embryos and larvae and the gross growth efficiency of juvenile and adult fish. Lasker (1962) Eldridge et al (1977) reported a yolk utilization efficiency of 0.74 for embryos and of 0.44 for larvae of Pacific herring. Similarly, the efficiency of converting yolk for embryos of other organisms is approximately 0.6 (Calow, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The energy content of a Balanion sp. prey item was estimated to be 0.3 mJ (Finlay & Uhlig 1981, Putt & Stoecker 1989, and that of 1 copepod nauplius to be 7.0 mJ (Lasker 1962, Houde & Schekter 1983.…”
Section: Methodsmentioning
confidence: 97%
“…Older larvae (>10 d post-hatching) fed on a greater range of prey types and sizes that included both nauplii and protozoans (Gallager et al 1996, Hunt von Herbing & Gallager 2000. Protozoans are small (30 to 50 µm), and swim in predictable patterns (Buskey et al 1993), and contain low total amounts of energy (Finlay & Uhlig 1981, Putt & Stoecker 1989, whereas copepod nauplii are larger (80 to 250 µm), swim faster, and provide an order of magnitude more energy than protozoans (Lasker 1962, Houde & Schekter 1983. Hunt von Herbing & Gallager (2000) found that first-feeding larval cod readily perceived and captured protozoans, but seemed less able to capture copepod nauplii because naupliar escape speeds were faster than larval maximal swimming speeds.…”
Section: Introductionmentioning
confidence: 99%